524 Investigating the genetic underpinning and associated audiological features of childhood hearing loss in Puerto Rico - Elinette Albino; Brenda Quiñones-Flores; Carmen Brewer; Rabia Faridi; Soami Santiago De Snyder; Thomas B. Friedman; Wanda M. Lugo Velez; Celinés Rodriguez-Acevedo; Carmen J. Buxo; Isabelle Roux (Journal of Clinical and Translational Science)
Objectives/Goals: Hearing loss (HL) can result from environmental and genetic factors. Some genetic variants may be more prevalent in populations living in geographic or cultural isolation. This study explores the genetic variants associated with HL in Puerto Rico and correlates these with auditory and balance disorders to uncover novel variants. Methods/Study Population: After obtaining individual informed consent and assent for a minor when applicable, we will collect clinical audiological data and biological samples (n  =  600) from families across Puerto Rico with a history of severe to profound HL. Genomic DNA will be extracted, and exome and mitochondrial genome sequencing will be conducted to identify causal variants in genes associated with HL. The study will assess the prevalence of both novel and reported variants in genes associated with HL and investigate founder variants in the Puerto Rican population. Involvement of genes so far not associated with HL will also be considered when a genetic diagnosis cannot be established. Auditory phenotypes will be correlated with genetic findings, allowing for a comprehensive analysis of genetic contributions to HL in this population. Results/Anticipated Results: This research will advance understanding of the genetic causes of HL in Puerto Rico, leading to more accurate diagnoses, personalized treatment options, and the discovery of novel genes associated with HL. It will also serve as an evidence-based reference to analyze the adequacy of current neonatal hearing screening protocols in PR. Recruitment and sample collection have begun, and we expect our findings to uncover population-specific variants. These results will provide a foundation for further genetic studies aiming at identifying the causes of HL in Puerto Ricans regardless of age of onset. Discussion/Significance of Impact: This study will enhance our understanding of hereditary HL and serve as a basis for developing population-specific diagnostic tools and interventions, particularly in the Puerto Rican population. The research will support future genetic studies and address health disparities in HL in the island.